The Construction Reality of Women Image as Patriarchal Objects in Indonesian Horror Film - Srilaksmi, Ida Ayu Alit; Damasemil, Calvin (Universitas Dian Nuswantoro, 2024)
As one of the film genres in Indonesia, horror films have different dynamics in terms of narrative and cinematography. The example is about the characterization of women in films. Women are often associated with victims, monsters, and other main characters in Indonesian horror films. This phase has an impact on the construction of reality in the image of women as a form of insertion of patriarchal culture in films. In patriarchal culture, women are formed through the depiction of figures full of negative emotions and synonymous with terror and revenge. This study aims to describe the forms of patriarchal culture towards women in Indonesian horror films from 1970-2022. This research uses literature study as the main method with related previous research. Based on this research, several connections were found regarding women who are depicted as objects of patriarchal culture with the main scope being the characterization of women as victims and monstrous feminine in 600 Indonesian horror films in the period 1970-2022. The image of women that is constructed has become a distinct pattern in Indonesian horror films because of the strong patriarchal culture. The commodification perspective according to the political economy of the media has increasingly strengthened the tendency of women to become objects in the Indonesian film culture. Women in horror films are often used as a mere commodity. In other words, women are indicated as an added value to become an exchange value in the horror film market.